Facile preparation of copper impregnated aluminum pillared montmorillonite: nanoclays for wastewater treatment - P. Tepmatee; P. Siriphannon (My University, 2016)
Abstract Copper impregnated aluminum pillared montmorillonites (Cu-iAlpill-MMTs) were prepared by adding Cu 2+ solution into dried aluminum polyohydroxy cation intercalated montmorillonite using various Cu 2+ concentrations, i.e. 4, 7, 10 and 13 wt% and then calcining at 500°C. The Cu-iAlpill-MMTs possessed slit-liked mesopores with pore diameters of 3.3–3.8 nm and ~6–35 nm as observed from the nitrogen adsorption isotherms. The mesopore quantities of Cu-iAlpill-MMTs gradually decreased with the increase of impregnated Cu 2+ concentrations. The impregnated CuO occupied not only the interior interlayers, but also the exterior surfaces of Cu-iAlpill-MMTs. The Cu-iAlpill-MMTs with 10 and 13 wt% of impregnated Cu 2+ could inhibit the growth of Escherichia coli . The Cu-iAlpill-MMTs effectively acted as the heterogeneous catalyst for removal reactive orange 16 (RO16) in Fenton or photo-Fenton oxidation treatments. The higher impregnated Cu 2+ and/or the longer treatment time brought about the higher percentage of RO16 removal.
Keywords: Layered Double Hydroxides Synthesis and Applications